GSK-3β Localizes to the Cardiac Z-Disc to Maintain Length Dependent Activation. Issue 6 (18th March 2022) - Stachowski-Doll, Marisa J.; Papadaki, Maria; Martin, Thomas G.; Ma, Weikang; Gong, Henry M.; Shao, Stephanie; Shen, Shi; Muntu, Nitha Aima; Kumar, Mohit; Perez, Edith; Martin, Jody L.; Moravec, Christine S.; et al.
Abstract : Background: Altered kinase localization is gaining appreciation as a mechanism of cardiovascular disease. Previous work suggests GSK-3β (glycogen synthase kinase 3β) localizes to and regulates contractile function of the myofilament. We aimed to discover GSK-3β's in vivo role in regulating myofilament function, the mechanisms involved, and the translational relevance. Methods: Inducible cardiomyocyte-specific GSK-3β knockout mice and left ventricular myocardium from nonfailing and failing human hearts were studied. Results: Skinned cardiomyocytes from knockout mice failed to exhibit calcium sensitization with stretch indicating a loss of length-dependent activation (LDA), the mechanism underlying the Frank-Starling Law. Titin acts as a length sensor for LDA, and knockout mice had decreased titin stiffness compared with control mice, explaining the lack of LDA. Knockout mice exhibited no changes in titin isoforms, titin phosphorylation, or other thin filament phosphorylation sites known to affect passive tension or LDA. Mass spectrometry identified several z-disc proteins as myofilament phospho-substrates of GSK-3β. Agreeing with the localization of its targets, GSK-3β that is phosphorylated at Y216 binds to the z-disc. We showed pY216 was necessary and sufficient for z-disc binding using adenoviruses for wild-type, Y216F, and Y216E GSK-3β in neonatal rat ventricular cardiomyocytes. One of GSK-3β's z-disc targets, abLIM-1 (actin-binding LIM protein 1), binds to the z-disc domains of titin that are important for maintaining passive tension. Genetic knockdown of abLIM-1 via siRNA in human engineered heart tissues resulted in enhancement of LDA, indicating abLIM-1 may act as a negative regulator that is modulated by GSK-3β. Last, GSK-3β myofilament localization was reduced in left ventricular myocardium from failing human hearts, which correlated with depressed LDA. Conclusions: We identified a novel mechanism by which GSK-3β localizes to the myofilament to modulate LDA. Importantly, z-disc GSK-3β levels were reduced in patients with heart failure, indicating z-disc localized GSK-3β is a possible therapeutic target to restore the Frank-Starling mechanism in patients with heart failure. Abstract : Supplemental Digital Content is available in the text.